Gestión técnica del sistema de gestión de seguridad y salud ocupacional en la dirección provincial de Orellana del ministerio de agricultura ganadería acuacultura y pesca período abril - octubre 2016. - Granda López, Cristian Bolívar (2017)
The objective of the present investigation was to carry out the Technical Management of the Occupational Health and Safety Management System at the Provincial Office of Orellana of the Ministry of Agriculture, Livestock Aquaculture and Fisheries in the period April - October 2016. The research work was carried out based on In the current regulations of the System of Work Risk Audits (SART), contemplating all the points of the Technical Management to obtain a technical and legal framework to decrease, identify, control, measure and monitor occupational hazards. A global observation of the whole company was carried out based on the legal technical requirements that must be met, by means of which the percentage of compliance was determined, which was very low. Then procedures were carried out to identify and evaluate the risks qualitatively. The technique used was the Identification, Evaluation, Measurement, Control and Health Surveillance through the application of Matrix GTC-45 (Colombian Technical Guide) for the purpose of analyzing, qualitatively and quantitatively evaluating all occupational hazards present in the 33 Work of the Provincial Directorate of Orellana of MAGAP. With the results of the Identification, Evaluation and Measurement of all the occupational hazards present in the Provincial Directorate of Orellana of MAGAP, a plan for the prevention of occupational hazards, as well as the permanent training in the field of industrial safety and Health in the work to all the personnel that work there. The present investigation helped to mitigate and eliminate all occupational risk factors present in the Provincial Office of Orellana of MAGAP, improving the working environment of the workers, safeguarding their physical and psychological integrity as well as the material assets of the management, creating a Culture of Prevention of Labor Risks. Reviewed by: Barriga, Luis Language Center Teacher